The Effect Of Current Ratio (Cr) And Return On Equity (Roe) On Stock Prices At PT. Aneka Tambang Tbk Period 2014-2023 - Fitriani, Indah; Ganar, Yulian Bayu (Doktoral Ilmu Manajemen, Universitas Pasundan, 2025)
This study aims to determine the effect of Current Ratio (CR) and Return On Equity (ROE) on Stock Prices at PT Aneka Tambang Tbk for the period 2014–2023. This study uses quantitative methods with various statistical analysis techniques, such as Descriptive Analysis, Classical Assumption Test, Linear Regression, Partial Test (t-Test), Simultaneous Test (F-Test), Determination Coefficient. The results of the study indicate that Current Ratio(CR) does not have a significant effect on Stock Price, as indicated by T count < T table -0.412 < 2.365 and a significance value of 0.692 > 0.05. On the other hand, Return On Equity (ROE) has a significant effect on Stock Price, with T count > T table 3.342 > 2.365 and a significance value of 0.012 < 0.05. while from the F test Current Ratio (CR) and Return On Equity (ROE) simultaneously have a significant effect on Stock Price, as indicated by F count > F table 5.979 > 4.737 and a significance value of 0.031 < 0.05. In addition, the coefficient of determination (R²) shows that 63.1% of Stock Price variability can be explained by existing variables, while the remaining 36.9% is influenced by other factors outside this study.